ANALISIS KOMPARATIF KINERJA KEUANGAN PERBANKAN BERDASARKAN METODE CAMELS DAN RGEC PADA PT. BANK MANDIRI (PERSERO) TBK. - Kusumawati, Melia (Jurnal Akuntansi AKUNESA, 2014)
This study to compare the financial performance of PT. Bank Mandiri (Persero) Tbk By using the CAMELS method and RGEC method. The data used is the 2010-2012 financial statements. From the results of the analysis showed that there was no significant difference between the results of the performance analysis RGEC method and CAMELS method. Mandiri Bank's financial performance during the years 2010-2012 was rated excellent. liquidity factors and sensitivity to market risk factors on the CAMELS method can be assessed on the risk factor profile RGEC method. Assesment system of Capital factor and earnings factor relative equal.Keywords : financial performance, CAMELS, RGEC